Reassessing the fighting performance of conscript soldiers during the Malvinas/Falklands War (1982) - Alejandro L. Corbacho (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2004)
While the idea is controversial, it is quite possible that, at least under certain circumstances, the fighting effectiveness of a conscript army can equal that of a professional army. For any army, fighting effectiveness is not only influenced by the degree of psychological cohesion among soldiers and officers, but also by the organizational culture of each particular service unit towards the preparation for war and the waging of the conflict itself. The Malvinas (Falklands) War of 1982 demonstrates this very well. In this war, two different types of armies confronted one another: the British army, a professional and all volunteer force, and the Argentine army constituted principally of conscripted soldiers. In this regard, some analysts assert that the British concept was vindicated when a force of British professional soldiers defeated an opposing Argentine force of draftees twice as numerous. Analysts in general have rated the capabilities of the Argentine land forces as poor, although there were exceptions and some units performed very well. These cases deserve to be studied. Notably, the most effective Argentine effort came from some small Army units and one Navy unit, the 5th Marine Battalion. For these units, two primary reasons account for the differences in fighting performance. First, small Army groups fought well because there was cohesion among their components, conscripts, noncommissioned officers, and junior officers, especially by the attitude of the latter. Secondly, in the case of the Marine battalion, its performance was the product not only of good training, but also of the different institutional approach to waging war that the Argentine Navy employed. These, in turn, improved cohesion. By focusing upon these units and their effectiveness, a rather new picture of the Malvinas War comes to light that differs quite substantially from those drawn in the immediate aftermath of the war itself. It should also make us rethink the lessons of the war, including those that surround the professionals versus conscripts controversy.
Keywords: 330; Militärökonomik; Falklandinseln